2006
DOI: 10.1111/j.1423-0410.2006.00756.x
|View full text |Cite
|
Sign up to set email alerts
|

Eliciting repeat blood donations: tell early career donors why their blood type is special and more will give again

Abstract: Sending out personalized, informative letters appears to be a potentially powerful donor-retention tool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 16 publications
(18 reference statements)
2
32
0
Order By: Relevance
“…Godin et al (2005) also found that having donated blood in the past and the shorter the length of time that elapsed since the last donation predicted a greater intention to donate in the near future. This is reinforced by Chamla et al (2006) who found that the more donors performed blood donations during the first year after their initial donation, the higher the probability that they would donate 6 months later.…”
Section: Literature Reviewmentioning
confidence: 84%
“…Godin et al (2005) also found that having donated blood in the past and the shorter the length of time that elapsed since the last donation predicted a greater intention to donate in the near future. This is reinforced by Chamla et al (2006) who found that the more donors performed blood donations during the first year after their initial donation, the higher the probability that they would donate 6 months later.…”
Section: Literature Reviewmentioning
confidence: 84%
“…For example, persons with sickle cell disease can require frequent transfusions and are at a high risk of developing alloantibodies; recruiting donors from racially diverse populations for blood antigen matching can reduce the risk of alloimmunization . New thresholds which have increased the minimum Hgb for male donors may have resulted in more deferrals of black males compared to other races, likely because healthy black males have been reported to have lower Hgb level than white males . Strategic planning tools to increase African‐American blood donation are available, but additional studies to determine effective methods to increase donations among minorities are needed …”
Section: Discussionmentioning
confidence: 99%
“…A possible approach to achieve this is to talk to replacement donors after their first donation, showing them the importance of donation and how their blood type is necessary. A study conducted by Chamla and coworkers 10 revealed that sending a personalized and informative letter to new donors increased the number returning to donate again. Another study showed that the shorter the donation interval between the first and next donation, the more likely the donor was to make subsequent donations 11 .…”
Section: Discussionmentioning
confidence: 99%